The lowest-lying excited singlet and triplet electronic states of propanal: An ab initio molecular orbital investigation of the potential energy surfaces - Buntine, Mark; Lee, C.; Metha, G. (Royal Society of Chemistry, 2004)
This study explores the potential energy surfaces of the S0, S1 and T1 states using ab initio theory to provide insight into the spectroscopy, photochemistry and reaction dynamics of propanal. Minima associated with the formyl potential energy coordinate in the S1 and T1 states are found to be ~60° out-of-phase with the S0 state. Furthermore, the excited states possess a pyramidal formyl carbon atom that leads to a double minimum at ±33° and ±49° for the S1 and T1 states, respectively. An exploration of the C–C dissociation coordinate on the T1 surface, yielding the products CH3CH2 + CHO, shows that a three-fold potential due to the formyl torsion is still operational, resulting in three unique transition states that lead to dissociation. The lowest energy pathway to dissociation occurs at a barrier height of 4766 cm−1 and the energy of the products is found to be 1017 cm−1, relative to the T1 global minimum. Consequently, a reverse barrier of 3749 cm−1 is calculated. Parameters calculated for the lowest energy transition state geometry are distinctly different from structures inferred from experiment, which assumed an isotropic dissociation channel.